2021
DOI: 10.1007/s00404-021-06337-8
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in women referred for colposcopy: a prospective observational study

Abstract: Purpose To evaluate the occurrence of anxiety in women attending a colposcopic examination within the new cervical cancer screening in Germany. Methods One hundred and fifty-six patients were asked to fill out Spielbergers STAI inventory form prior to their colposcopic examination. For the statistical analysis, a two by two between-group design was applied including the following group factors: the repeat factors included patients, who presented to our cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Compared with other studies that measure anxiety levels before and after colposcopy, we found an overall low STAI median score for anxiety, despite that women in our study were informed that, if they were eligible, they would be offered a diagnostic LLETZ 10,11,26–28 . This could partly be explained by differences in age distribution, as the median age in the present study was 67.7 years (IQR 61.6–70.3 years) compared with the above mentioned studies that had mean ages ranging from 29.0 to 45.6 years.…”
Section: Discussioncontrasting
confidence: 90%
“…Compared with other studies that measure anxiety levels before and after colposcopy, we found an overall low STAI median score for anxiety, despite that women in our study were informed that, if they were eligible, they would be offered a diagnostic LLETZ 10,11,26–28 . This could partly be explained by differences in age distribution, as the median age in the present study was 67.7 years (IQR 61.6–70.3 years) compared with the above mentioned studies that had mean ages ranging from 29.0 to 45.6 years.…”
Section: Discussioncontrasting
confidence: 90%
“… 2 14 25 26 Medical appointments are an anxiety-provoking experience for patients, especially for those facing a possible or existing malignant diagnosis. 27 The word ‘distress’ is mentioned by patients with cancer who were denied the option of having a family member or friend with them during medical appointments. 15 Although the respondents in this study endorsed vigilant sanitary precautions to prevent nosocomial infections, an overwhelming proportion (75.0%) supported the possibility of being accompanied by a significant other during medical consultations, irrespective of their demographic, disease-specific or pandemic-specific characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In younger women especially, there is high transient incidence of HPV, and using HPV infection alone as a screening modality would result in an unacceptably high false detection rate of CIN2+. False positive results not only induce anxiety7 8 in patients but also lead to potential overtreatment, with the potential to overwhelm colposcopy services unless these are robustly designed 3 9…”
Section: Introductionmentioning
confidence: 99%